Comparison of retinochoroidal vascular and structural changes after half-dose photodynamic therapy versus half-fluence photodynamic therapy based on optical coherence tomography angiography in eyes with chronic central serous chorioretinopathy - (:unkn) unknown (My University, 2022)
Purpose: The aim of this study is to compare the efficacy of half-fluence photodynamic therapy (PDT) and half-dose PDT on the choroidal structure via perfusion of the retinal plexus and choriocapillaris in eyes with chronic central serous chorioretinopathy (cCSCR). Materials and Methods: This retrospective study included 43 eyes in 43 patients with cCSCR. Patients in group 1 received half-fluence (verteporfin 6 mg m(-2)) PDT and those in group 2 received half-dose (verteporfin 3 mg m(-2)) PDT. Enhanced depth imaging optical coherence tomography and optical coherence tomography angiography (OCTA) images were recorded 1 day before and 3 months after PDT. Total choroidal area (TCA), luminal area (LA), and stromal area (SA) were calculated using Image J software. Results: From baseline to 3 months post PDT TCA decreased from 2.43 +/- 0.47 mm(2) to 2.08 +/- 0.59 mm(2) (p < 0.001), LA decreased from 1.78 +/- 0.11 mm(2) to 1.54 +/- 0.26 mm(2) (p < 0.001), and SA decreased from 0.76 +/- 0.33 mm(2) to 0.53 +/- 0.37 mm(2) (p < 0.001) in group 1. Choriocapillaris vascular density measured via OCTA increased from 37.82 +/- 10.99 at the initial visit to 44.96 +/- 15.34 at month 3 after half-fluence PDT administered to the fovea (p < 0.001). Deep capillary plexus vessel density was 32.49 +/- 11.36 at baseline and increased to 43.27 +/- 11.40 at month 3 after half-fluence PDT administered to the fovea (p < 0.001) in group 1. TCA decreased to 2.00 mm(2) +/- 0.51 mm(2) from 2.39 mm(2) +/- 0.43 mm(2) (p < 0.001), LA decreased to 1.53 +/- 0.29 mm(2) from 1.74 +/- 0.16 mm(2) (p = 0.019). Although SA decreased from 0.76 +/- 0.33 mm(2) to 0.53 +/- 0.37 mm(2) in group 2, the difference was not significant (p = 0.07). Based on OCTA, choriocapillaris vascular density increased from 43.68 +/- 10.38 mm(2) at baseline to 47.46 +/- 6.42 mm(2) at 3 months after half-dose PDT onto the fovea (p = 0.049). Deep capillary plexus vessel density increased from 34.37 +/- 9.36 mm(2) at the initial visit to 38.17 +/- 8.81 mm(2) 3 months after half-dose PDT onto the fovea (p = 0.046) in group 2. At 3 months, post-PDT subretinal fluid (SRF) was significantly higher resolution in group 1 than in group 2 (p = 0.021). Conclusions: OCTA shows there is a significant increase in deep capillary plexus and choriocapillaris perfusion 3 months after both half-fluence PDT and half-dose PDT. Although there was a significant decrease in LA in both groups, based on OCTA there was a significant decrease in SA, a significant increase in choriocapillaris and deep capillary perfusion in group 1; therefore, the level of SRF resolution at month 3 post PDT might explain its higher incidence in group 1.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; OFTALMOLOJİ; Klinik Tıp; Klinik Tıp (MED); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Optometri; Oftalmoloji; Optometry; Ophthalmology